A drop‐in centre for treating mental health problems in children with chronic illness: Outcomes for parents and their relationship with child outcomes. Issue 4 (25th October 2021) - Bennett, Sophie D.; Kerry, Eleanor; Fifield, Kate; Ching, Brian C. F.; Catanzano, Matteo; Liang, Holan; Heyman, Isobel; Coughtrey, Anna E.; Sanderson, Charlotte; Rojas, Natalia; Shafran, Roz
Abstract: Background: Children with chronic health conditions and their parents are at greater risk of developing emotional and behavioural problems compared to their physically healthy peers. The psychological impact on parents is crucial to understand given the relationship between parental mental health and child emotional and behavioural difficulties. This study was part of a broader research project examining the acceptability, feasibility and impact of a 'Mental Health and Psychological Wellbeing Drop‐in Centre' in a paediatric hospital providing access to support and intervention for children and their families. This paper aimed to investigate the impact of the centre on parents ( n = 148). Methods: Parental anxiety and depression were assessed using the GAD‐7 and PHQ‐9 at baseline and 6‐month post‐baseline. Child mental health was assessed using the parent‐report Strengths and Difficulties Questionnaire (SDQ). If parents had significant mental health needs, a brief intervention/signposting to relevant services was provided. Results: At baseline, 48% of parents scored above clinical threshold for anxiety and 41% for depression, and parent reported child SDQ scores were correlated with parental anxiety and parental low mood. Self‐reported parental anxiety and low mood decreased at 6‐months post‐baseline (parental anxiety: mean decrease = 2.29 [1.22–3.36], d = 0.38; parental low mood: mean decrease = 1.81 [0.64–3.00], d = 0.28). There were no significant correlations between change in parent reported child wellbeing and changes in parental low mood and anxiety between baseline and 6‐month post‐baseline. Conclusions: Assessing and providing a brief treatment to address the mental health needs of parents of children with comorbidity may bring important benefits. It is recommended that children's mental health services consider assessment of parental mental health as part of routine care.